2021
DOI: 10.3389/fimmu.2021.677730
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Organ Transcriptomic Analysis of Rainbow Trout Infected With Ichthyophthirius multifiliis Through Co-Expression and Machine Learning

Abstract: Ichthyophthirius multifiliis is a major pathogen that causes a high mortality rate in trout farms. However, systemic responses to the pathogen and its interactions with multiple organs during the course of infection have not been well described. In this study, dual-organ transcriptomic responses in the liver and head kidney and hemato-serological indexes were profiled under I. multifiliis infection and recovery to investigate systemic immuno-physiological characteristics. Several strategies for massive transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Support vector machine (SVM) was used to classify caste across the species. We note that SVMs are more commonly used on larger datasets 83 , but is known to have reasonable success with small datasets 84 where there are thousands of features (genes) can be used to classify smaller numbers of samples. In brief, this analysis involved taking species-scaled, logged and normalised gene expression data from the nine species (with one replicate for the queen and worker sample), filtering the lowly expressed genes, splitting into training and testing datasets (8 training, 1 testing), creating an SVM classifier that best separates caste in the training species (finding the best gamma and C tuning variables) and testing the one species left out, resulting in a caste classification.…”
Section: Methodsmentioning
confidence: 99%
“…Support vector machine (SVM) was used to classify caste across the species. We note that SVMs are more commonly used on larger datasets 83 , but is known to have reasonable success with small datasets 84 where there are thousands of features (genes) can be used to classify smaller numbers of samples. In brief, this analysis involved taking species-scaled, logged and normalised gene expression data from the nine species (with one replicate for the queen and worker sample), filtering the lowly expressed genes, splitting into training and testing datasets (8 training, 1 testing), creating an SVM classifier that best separates caste in the training species (finding the best gamma and C tuning variables) and testing the one species left out, resulting in a caste classification.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative aspect of the enriched KEGG pathways can be judged by comparing the sizes of the pie charts (the bigger the pie, the larger the proportion of enriched pathways). The colors of sectors, representing the higher-level functional categories defined according to the KEGG database ( (accessed on 16 September 2022)) and the previous study [ 26 ], can help to visually identify the changes in gene functional categories and allow a rough comparison of the qualitative aspects of the transcriptional change ( Figure 3 and Table S5 ). In the present study, both the normalized and non-normalized datasets yielded very similar results ( Tables S5 and S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The focal adhesion pathway acts as a signal sensor to mediate signal transduction and the immune response to stimuli. Indeed, a previous study has shown that parasitic infection ( I. multifiliis ) stimulated the focal adhesion pathways in rainbow trout ( Roh et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%